Portraying violence in the Hebrew Bible a literary and cultural study - Lynch, Matthew J. 1979- (New York University of Cambridge ESOL Examinations, 2020)
Examines four key ways that writers of the Hebrew Bible conceptualize and critique acts of violence.
Description based on publisher supplied metadata and other sources
Keywords: Violence in the Bible; Electronic books